2014
DOI: 10.1038/ncomms4073
|View full text |Cite
|
Sign up to set email alerts
|

PTPN2 attenuates T-cell lymphopenia-induced proliferation

Abstract: When the peripheral T-cell pool is depleted, T cells undergo homoeostatic expansion. This expansion is reliant on the recognition of self-antigens and/or cytokines, in particular interleukin-7. The T cell-intrinsic mechanisms that prevent excessive homoeostatic T-cell responses and consequent overt autoreactivity remain poorly defined. Here we show that protein tyrosine phosphatase N2 (PTPN2) is elevated in naive T cells leaving the thymus to restrict homoeostatic T-cell proliferation and prevent excess respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 60 publications
5
85
1
Order By: Relevance
“…4D). Ptpn2 is a negative regulator of Jak3/Stat5 signaling that has been shown to restrain homoeostatic T-cell responses (29). Furthermore, knockdown of PTPN2 in human T-cell acute lymphoblastic leukemia increased the proliferation and cytokine sensitivity of leukemic cells (30), a phenotype closely resembling the effects of miR-155 overexpression in our model.…”
Section: Mir-155 Inhibits Multiple Negative Regulators Of Akt and Stamentioning
confidence: 61%
“…4D). Ptpn2 is a negative regulator of Jak3/Stat5 signaling that has been shown to restrain homoeostatic T-cell responses (29). Furthermore, knockdown of PTPN2 in human T-cell acute lymphoblastic leukemia increased the proliferation and cytokine sensitivity of leukemic cells (30), a phenotype closely resembling the effects of miR-155 overexpression in our model.…”
Section: Mir-155 Inhibits Multiple Negative Regulators Of Akt and Stamentioning
confidence: 61%
“…Although the hurdle of developing of selective PTP1B and TCPTP inhibitors has been demonstrably overcome, a significant albeit not insurmountable challenge remains in selectively targeting the brain. This is particularly important for TCPTP given its role in hematopoietic development and autoimmunity [112][113][114][115]. Although TCPTP heterozygous deficiency does not result in any overt immune phenotype [112], TCPTP heterozygoisty is sufficient to enhance T cell responses to self-antigen and autoimmunity, with age [115], in the context of lymphopenia [113] and in a mouse model of type 1 diabetes [114].…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important for TCPTP given its role in hematopoietic development and autoimmunity [112][113][114][115]. Although TCPTP heterozygous deficiency does not result in any overt immune phenotype [112], TCPTP heterozygoisty is sufficient to enhance T cell responses to self-antigen and autoimmunity, with age [115], in the context of lymphopenia [113] and in a mouse model of type 1 diabetes [114]. Despite this, recent work aimed at improving wholebody insulin sensitivity through the intranasal application of insulin and the enhancement of hypothalamic and parasympathetic outputs in humans [47,48,74,116], suggests that selective CNS delivery of PTP1B/TCPTP inhibitors might be a viable option.…”
Section: Discussionmentioning
confidence: 99%
“…When PTPN2 function is lost in IECs, the body seems to be able to compensate this shortcoming. However, in vivo studies using other tissue-specific PTPN2 knock out mouse strains have already demonstrated the importance of this phosphatase for the development of CD4 + cells [28] but also for TCR signalling and lymphopenia-induced proliferation in CD8 + cells [29,30] . Apparently, loss of PTPN2 in the T cell compartment cannot be counterbalanced and leads to strong phenotypes.…”
Section: Discussionmentioning
confidence: 99%